Preparation and Photocatalytic Activity of Magnetic Fe3O4/SiO2/TiO2 Composites - Rijing Wang; Xiaohong Wang; Xiaoguang Xi; Ruanbing Hu; Guohua Jiang (Advances in Materials Science and Engineering)
A simple sol-gel method was used to prepare magnetic Fe3O4/SiO2/TiO2 composites with core-shell structure. Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), and transmission electron microscopy (TEM) have been applied to investigate the structure and morphology of the resultant composites. The obtained composites showed excellent magnetism and higher photodegradation ability than pure TiO2. The photocatalytic mechanism was also discussed. The magnetic composites should be extended to various potential applications, such as photodegradation, catalysis, separation, and purification processes.